Between the ritual and the commercial. Ethnographic reflections about the religious practices of the Worldwide Missionary Movement in Lima, Peru - Rolleri, Jair (2018)
This article proposes an ethnographic discussion about economic rituals in Lima Pentecostalism and, particularly, in the case of the Christian Pentecost Church “Worldwide Missionary Movement”. To do this, draw a theoretical course on studies that, from anthropology and sociology of religion, have been developed with respect to the rituality, the Protestant phenomenon and its presence in Peru. In that sense, we return to the works of Turner, Rappaport, Berger, Luckmann, Marzal and Bastian. To understand the rituality of the Movement, an ethnographic study of seven months was developed in the central temple of the Presbytery N ° 7 of the Worldwide Missionary Movement, located in Pueblo Libre, Lima. As a main result of this research, we found that the religious practices of this Church shows a hybridization between the ritual and the corporate, that is, between the behavior motivated by faith and the strategy for the business logic that, in turn, structure the social life of this congregation.